Introduction to the Monothematic Block: Socio-Political Resilience vis-à-vis the Contemporary World Crises - Alice Koubová; Ondřej Lánský (Filozofia)
Introduction to the monothematic block: Socio-Political Resilience vis-à-vis the Contemporary World Crises.